A Novel Application of Laser in Biocontrol of Plant Pathogenic Bacteria - Nermin El Semary; Haifa Al Naim; Munirah F. Aldayel (Applied Sciences, 2022)
The effect of laser radiation has never been tested on the antimicrobial activity of cyanobacterial extracts. In order to investigate this, aqueous extracts from three cyanobacterial strains identified as Thermoleptolyngbya sp., Leptolyngbya sp., and Synechococcus elongatus were exposed to laser radiation. The aqueous extracts both directly exposed to the laser and those derived from pre-exposed biomass were tested for their antimicrobial activity to select the most active extracts under different exposure times and distances from the laser source. Methods: A fixed weight of one-month old cyanobacterial biomass was used in extraction. Another similar biomass was exposed to laser before aqueous extraction. The laser treatment was performed using two distances, 5 and 10 cm, with three exposure times, 4, 16, and 32 min. The antimicrobial assay was performed against the bacterial plant pathogen, whose identity was confirmed by molecular analysis and cell wall structure by a Gram stain. Results: The pathogenic bacterium was identified as Gram-negative Pantoae vagans. The aqueous extract that was not exposed to laser treatment (control) was mostly ineffective against the pathogenic bacterium, whereas a significant increase in the antimicrobial effect was observed for the extract directly exposed to the laser followed by the extract derived from laser-pre-exposed cyanobacterial biomass. In the case of Synechococcus elongatus extracts, the extract that was directly exposed to the laser showed the highest statistically significant antimicrobial activity against Pantoea vagans, with an inhibition zone of 15.5 mm, at 10 cm and 4 min of laser treatment. Conclusions: This is the first report on the effect of laser on enhancing the antimicrobial profile of cyanobacterial extracts. The direct exposure of cyanobacterial extracts to the laser was more effective and biologically safer than exposing the biomass itself prior to extraction. The laser used was a monochromatic red light within the visible range. This radiation increased the antimicrobial activity of cyanobacterial extracts and can be used as an eco-friendly biocontrol strategy.